AUDIT KOMUNIKASI KOMUNITAS GIRL UP SEMARANG - Via Oktarina, Rafida; Luqman, Yanuar; Dwiningtyas Sulistyani, Hapsari (Interaksi Online, 2024)
The Girl Up Semarang Community is a community that operates in the field of feminism which is directly supported by Girl Up Indonesia as a form of initiation by the United Nations Foundation to make SDGs Number 5 Gender Equality a success. As one of the largest communities in Semarang and with the power they have, they still lack the ability to create an interactive climate through their social media, this also applies to the campaign process they carry out, where there is a lack of participants in every campaign they carry out, However, despite this, Girl Up Semarang always strives to remain active both internally and externally in building effective and efficient communication with their audience.This research is qualitative research using the SWOT analysis method. Through interviews conducted with 5 respondents, it was found that the results of the SWOT analysis showed that on the IFE matrix Girl Up Semarang had the highest weight on the attractive branding factor with a weight of 0.30 and on the EFE matrix it had the highest weight on the online campaign factor, and the last one in the SPACE matrix shows that a good strategy that should be used is an aggressive strategy. This means that Girl Up Semarang has attractive branding qualities to be able to form a positive response from the public towards Girl Up Semarang with campaigns and various information that they distribute through their social media.